Hydrothermal synthesis of PANI/MXene nanocomposite exhibiting metamaterial-like dielectric behavior - Demirelli, Kadir; Ercan, Cemile; Bachkol, Darwn Hassan Kak; Abubakar, Abdullahi Musa; Dere, Aysegul; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2025)
A highly efficient exfoliated 2D h-T3C2Tx (h-MXene) was prepared by hydrothermal etching route with low toxicity etching agents (NaBF4, HCl). The oxidative polymerization of polyaniline (PAN) is led to environmentally friendly, widespread applications and open the way for many researchers. The h-T3C2Tx h-MXene produced by hydrothermal etching route was found to have a higher interlayer distance compared to that prepared by conventional HF etching. The h-PANI and h-T3C2Tx h-MXene0.25-h-PANI nanocomposites were characterized by Fourier-Transform Infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX) and X-ray diffraction (XRD) techniques. The frequency dependence of conductivity and dielectric measurements were carried out at various voltages in the range of 200 Hz to 10 MHz at room temperature for the nanocomposite with h-PANI and h-MXene produced by hydrothermal method. To investigate the potential of h-MXene as a conductive filler, it was added to the h-PANI matrix for dielectric applications and compared with that of h-PANI. The Cole-Cole plots for both h-PANI and h-Ti3C2Tx MXene0.25/h-PANI nano-composite indicate a single semicircle indicating that the conductivity is due to the hopping of charge carriers. The obtained results suggest that h-PANI and h-Ti3C2Tx MXene0.25/h-PANI nanocomposite with negative dielectric permittivity can be envisioned for applications such as subwavelength imaging, invisibility.
Keywords: H-PANI; H-Ti 3 C 2 Tx; Nanocomposite; Hydrothermal method; Dielectric contant; Cole-Cole plot